An overview of cognitive aspects of β-carbolines - Heshmati, Pooneh; Nasehi, Mohammad; Zarrindast, Mohammad Reza (Archives of Advances in Biosciences, 2013)
Mind-altering drugs, especially plants, have fascinated human and always occupied man’s attention .Among the plants used by humans, those able to alter the mind and the mood have drawn special consideration. Actually, due to their amazing effects, these drugs, have occupied much of the researchers’ time and efforts towards attempts to understand their mechanism, and, hence, to understand human thoughts, behavior, cognitive aspects, sensations and etc. The fact is plants could have beneficial properties to treat mental disease and have some effects on cognitive function. Now we know that plants by originating directly from nature are not less toxic than synthetic drugs. The manner of poisoning with plants can be divided into unintentional or intentional ingestion of plant material and substance abuse. This review article deals with β-carboline, which has effect on CNS.